Creating low energy paint surface using hollow sub-micron-latex particles - ARCA, EMİN; EROĞLU, MEHMET SAYIP (ELSEVIER SCIENCE SA, 2016)
In this study, core-shell hollow nano-particles in latex form (nano-HLPs) were successfully prepared by using a hydrophobic styrene/methyl methacrylate mixture as shell materials and methacrylic acid/methyl methacrylate/butyl acrylate as core material. Scanning electron microscopy (SEM) images and dynamic light scattering measurements showed that the HLPs had average size of 600 nm. The nano-HLPs were used to obtain more hydrophobic paint surfaces. They were mixed with water based acrylic outdoor paint in different proportions and applied to metal surfaces. The coated surfaces were kept at 60 degrees C and 80 degrees C for 1 h to allow the nano-HLPs to move to the surface, which resulted in their surface enrichment. Thus, more hydrophobic paint surfaces were obtained. The changes in surface energy values of the coated surfaces with temperature and composition were followed by contact angle measurements using Young-Dupre equation. The surface energy was observed to decrease with increasing temperature and nano-HLPs portion of the outdoor paint. (C) 2016 Published by Elsevier B.V.
Keywords: Nano-hollow latex particles (nano-HLPs); Core-shell polymer; Hydrophobic coating surfaces; Contact angles; Surface energy; POLYMER